2009
DOI: 10.4038/rjs.v4i0.56
|View full text |Cite
|
Sign up to set email alerts
|

Microbial transformation of sesquitepenoid ketone, (+) Nootkatone by <i>Macrophomia phaseolina</i>

Abstract: Microbial transformation is an effective tool for the structural modification of bioactive natural and synthetic compounds leading to synthesis of more potent derivatives. Its application in asymmetric synthesis is increasing due to its versatility and ease. This article presents biotransformation of sesquiterpenoid ketone, (+)-Nootkatone (1) by M. phaseolina, a plant pathogenic fungus. The transformation afforded four main compounds. They were determined to be 1:6 stereoisomeric mixture of 11,12-dihydroxy-11,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 13 publications
(7 reference statements)
0
2
0
Order By: Relevance
“…(+)-Nootkatone was transformed also by the plant pathogenic fungus Macrophomia phaseolina, giving rise to four main compounds, two of them in stereoisomeric mixture. The substrate and two other products, 13-hydroxynootkatone and 12-hydroxy-11,12-dihydroxynootkatone, revealed significant antiprotozoal activity [109].…”
Section: Substrate Additionmentioning
confidence: 94%
“…(+)-Nootkatone was transformed also by the plant pathogenic fungus Macrophomia phaseolina, giving rise to four main compounds, two of them in stereoisomeric mixture. The substrate and two other products, 13-hydroxynootkatone and 12-hydroxy-11,12-dihydroxynootkatone, revealed significant antiprotozoal activity [109].…”
Section: Substrate Additionmentioning
confidence: 94%
“…Phytochemical tests for flavonoids, saponins, lactones, phenolic hydroxyls, unsaturation, coumarins, alkaloids, sesquiterpene lactones, steroids, terpenes, carbonyl groups, sugars, and anthocyanins were performed on both plant material and C. citratus EO using previously reported methodologies [ 23 , 24 , 25 ].…”
Section: Methodsmentioning
confidence: 99%
“…Ethyl-acetate extracted a wider range of Source: Ramavhale, T.T., 2024, 'Isolation, structure elucidation, antimicrobial activity, and effects of plant extracts used for the treatment of "u wela"', PhD thesis, University of Limpopo compounds of polar alkaloids, non-polar lipids, as well as essential oils. Acetone isolates non-polar fats, oils, and specific non-polar secondary metabolites (Bulugahapitiya 2013). Other researchers found that acetone can dissolve both polar and non-polar compounds (Maulidiyah et al 2023).…”
Section: Extraction Of Plant Materials Using Different Solventsmentioning
confidence: 99%